International law, indicators and global governance - Estrada Tanck, Dorothy (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
The use of indicators in international law and global governance has recently developed as a basis for evaluation, decision-making and conceptual and methodological legitimation. This study will analyse the use of different measurement devices constructed at the international level. It will consider the assessment of the state of human security as a case study, placing a particular focus on the relationship of ‘narrow’ and ‘broad’ views of human security to all human rights: civil, political, economic, social and cultural, and incorporating the aggravated human security risks encountered globally by women and girls. As a result, the text presents a proposal of a more holistic and operational measurement of human security based on a gendered and human rights based-approach.